Residual Cyst in an Elderly Patient: A case report with brief review of literature - Patil, Santosh R; Yadav, Nidhi; Alam, Fayyaz; Gudimaneni, Ravi Kumar; S, Shailaja; Alam, Mohammad Khursheed (International Journal of Human and Health Sciences (IJHHS), 2018)
The term residual cyst is used for a cyst that has persisted after its associated tooth has been extracted or lost. Residual cysts are commonly observed in males and frequently found in the anterior region of the maxillary jaw. Residual cysts are among most common cysts of the jaws and are generally asymptomatic. We are reporting a case of residual cyst in the mandible of a 59-year-old male patient with emphasis on the pathogenesis, clinical, radiological features and treatment aspects. International Journal of Human and Health Sciences Vol. 02 No. 02 April’18. Page : 87-90